Photo cleavable thioacetal block copolymers for controlled release. Issue 25 (11th June 2021) - Men, Yongjun; Brevé, Tobias G.; Liu, Huanhuan; Denkova, Antonia G.; Eelkema, Rienk
Abstract : The o -nitrobenzene thioacetal group selectively cleaves upon UV-A irradiation. When incorporated in a block-copolymer, these photoactive groups can be used for controlled release of molecular cargo from polymer nanoparticles. Abstract : We present a new light cleavable polymer containing o -nitrobenzene thioacetal groups in the main chain. By conjugation to a PEG block, we synthesized block copolymers capable of forming nanoparticles in aqueous solution. We studied drug encapsulation and release using the model drug Nile Red. Irradiation with UV-A light (365 nm) leads to efficient degradation of the polymers and associated burst release of the payload. Unlike other thioacetal and thioketal polymers, these polymers are stable to reactive oxygen species (ROS), preventing non-triggered release. Moreover, the nanocarriers showed low cytotoxicity in cell viability experiments.